2018
DOI: 10.1186/s11671-018-2672-5
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Ultraviolet Photodetector Based on Graphene Quantum Dots Decorated ZnO Nanorods/GaN Film Isotype Heterojunctions

Abstract: A novel isotype heterojunction ultraviolet photodetector was fabricated by growing n-ZnO nanorod arrays on n-GaN thin films and then spin-coated with graphene quantum dots (GQDs). Exposed to UV illumination with a wavelength of 365 nm, the time-dependent photoresponse of the hybrid detectors manifests high sensitivity and consistent transients with a rise time of 100 ms and a decay time of 120 ms. Meanwhile, an ultra-high specific detectivity (up to ~ 1012 Jones) and high photoresponsivity (up to 34 mA W−1) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…Moreover, the presence of GQDs also helps in faster collection of the photogenerated charge carrier, leading to reduced response time. Lately, Liu et al have reported a GQD-sensitized ZnO-NRs/GaN-film (metal organic chemical vapor deposition) heterostructure-based UV photodetector; however, the reported responsivity of the detector is very low (∼34 mA/W) even at a very high applied bias voltage of 10 V. 31 In this work, we have reported the fabrication of a highperformance UV photodetector utilizing the unique ZnO-NR/ GaN-NT/heterostructure sensitized with GQDs. The analysis exhibits the cumulative effect of the ZnO/GaN heterointerface junction (their nanostructures implicated higher surface to volume ratio) and extra photoinduced charge carriers via GQD sensitization with efficient transport by a ■ METHODS/EXPERIMENTAL SECTION ZnO-NR/GaN-NT Heterostructure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, the presence of GQDs also helps in faster collection of the photogenerated charge carrier, leading to reduced response time. Lately, Liu et al have reported a GQD-sensitized ZnO-NRs/GaN-film (metal organic chemical vapor deposition) heterostructure-based UV photodetector; however, the reported responsivity of the detector is very low (∼34 mA/W) even at a very high applied bias voltage of 10 V. 31 In this work, we have reported the fabrication of a highperformance UV photodetector utilizing the unique ZnO-NR/ GaN-NT/heterostructure sensitized with GQDs. The analysis exhibits the cumulative effect of the ZnO/GaN heterointerface junction (their nanostructures implicated higher surface to volume ratio) and extra photoinduced charge carriers via GQD sensitization with efficient transport by a ■ METHODS/EXPERIMENTAL SECTION ZnO-NR/GaN-NT Heterostructure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In another work, a high‐performance GQD‐decorated ZnO nanorods/GaN film was fabricated for UV monitoring. [ 217 ] In this heterojunction, GQDs act as electron donors and contribute to the enhancement of the active carrier concentration.…”
Section: Applications Of Gqdsmentioning
confidence: 99%
“…Meanwhile, an ultra-high specific detectivity of 10 12 Jones was obtained. The improved performance was due to the rapid separation of photogenerated electrons and holes and efficient carrier migration [122].…”
Section: ) Conventional Vertical P-n Heterojunction-based Ultraviolementioning
confidence: 99%